Pengembangan Media Pembelajaran E-SKI untuk Meningkatkan Prestasi Belajar Kelas VII di MTs Plus Bahrul Ulum Tambakberas Jombang - Rudiyanto, Nur Faiq; Nisa’, Khoirun; Wahyudi, Wahyudi (YASIN, 2025)
The low student interest in learning, which is still dominated by lecture methods and conventional textbooks, underlies the development of audiovisual-based learning media for the subject of Islamic Cultural History (SKI). This study aims to develop the E-SKI application based on Information and Communication Technology (ICT) to improve the learning achievement of seventh-grade students at MTs Plus Bahrul Ulum. The Research and Development (R&D) method using the ADDIE model was employed, encompassing the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of 21 seventh-grade students. Data were collected through observation, interviews, and questionnaires. Content validation by experts yielded an average score of 89.3% (very good category), and media validation by media experts achieved 93.3% (very good category), indicating that the media product is feasible for trial. Field testing resulted in a score of 88.1% (good category), demonstrating that the E-SKI media on the topic “The Rightly Guided Caliphs and the Umayyad Dynasty” is effective for use in SKI learning processes. This study is expected to inspire students to utilize technology in learning, thereby maintaining motivation and enthusiasm in pursuing beneficial and sustainable knowledge.